Predictors of Acute Kidney Injury in Critically Ill Patient at Intensive Cardiac Care Unit - Jauhari, Haris; Bagaswoto, Hendry Purnasidha; Setianto, Budi Yuli (Jurnal Kardiologi Indonesia, 2025)
In “Predictors of Acute Kidney Injury in Critically Ill Patient at Intensive Cardiac Care Unit” (Indonesian Journal of Cardiology, 43(4), 144-9. https://doi.org/10.30701/ijc.1322), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1322. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1322